Priorytety rozwoju infrastruktur technicznej i społecznej na przykładzie gmin województwa lubelskiego - Myna, Artur (Priorities of Technical and Social Infrastructure Development on the Example of the Municipalities of the Lublin Voivodship, 2006)
The aim of this work is a presentation of gminas' development priorities in the Lublin voivod-ship, which are reflected by the investment expenditure structure of municipalities and their plans of development of technical and social infrastructure. From the standpoint of objectives and investment priorities, three types of municipalities can be distinguished: (1) overcoming elementary barriers to development (investing in basic technical infrastructure facilities - water mains, roads), (2) overcoming development thresholds (mainly in the area of the capital-consuming environment protection facilities) and (3) investing in higher-order social infrastructure. The results of the study indicate that there are three main stances of the municipalities in formation of infrastructures' development priorities. They are: adjusting priorities to preferences of institutions that co-finance public investments, formulating too many priorities in relation to investment potential and connecting priorities with the implementation of development programmes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 698-704